Increased Signal Complexity Improves the Breadth of Generalization in Auditory Perceptual Learning - David J. Brown; Michael J. Proulx (Neural Plasticity)
Perceptual learning can be specific to a trained stimulus or optimally generalized to novel stimuli with the breadth of generalization being imperative for how we structure perceptual training programs. Adapting an established auditory interval discrimination paradigm to utilise complex signals, we trained human adults on a standard interval for either 2, 4, or 10 days. We then tested the standard, alternate frequency, interval, and stereo input conditions to evaluate the rapidity of specific learning and breadth of generalization over the time course. In comparison with previous research using simple stimuli, the speed of perceptual learning and breadth of generalization were more rapid and greater in magnitude, including novel generalization to an alternate temporal interval within stimulus type. We also investigated the long term maintenance of learning and found that specific and generalized learning was maintained over 3 and 6 months. We discuss these findings regarding stimulus complexity in perceptual learning and how they can inform the development of effective training protocols.